An Analysis of Translation Techniques in translating Enola's Utterances in Enola Holmes Movie - Putra, Dhanu Ario; Nopriansah, Nopriansah; Ependi, Selviyan; Mutmainah, Yeni (Journal Of Dehasen Educational Review, 2020)
Translation nowadays can generally be understood as an effort to transfer the source language to the target language. expert states that in the field of languages, translation today has several meanings, namely first is the general subject field or phenomenon, second is the product that is the text that has been translated, third is the process of producing the translation, otherwise known as translating. In terms of the translation itself, researchers can pay more attention to translation products where translator translates by reading the entire text and translating the source language into the target language. This research aims to describe the translation techniques used by HaiBunda.com in translating the English movie entitled "Enola Holmes" into Indonesian based on Vinay and Darbelnet (1958), namely borrowing, calque, literal translation, transposition, modulation, equivalence and adaptation. The data in this study was conducted using qualitative methods. This research revealed that the most dominant technique used by the translator was the literal translation technique, with a total of about 21 times. In addition, translator prefer to use the literal translation technique because the translator use word-for-word translation in translating the text. It shows that the translator aims to maintain a close correspondence between the source language and the target language, preserving as much of the original words and structures as possible. Keyword: translation, translation technique